NiO-YSZ anode composite material derived from mechano-chemical for solid oxide fuel cells application - Srisuwan, Thanakorn; Puengjinda, Pramote; Kaewtrakulchai, Napat; Chanpee, Sirayu; Jadsadajerm, Supachai; Panomsuwan, Gasidit; Ruttanadech, Nuttapong; Wongrekdee, Sutthipoj; Chollacoop, Nuwong; Faungnawakij, Kajornsak; Fuji, Masayoshi; Eiad-ua, Apiluck (My University, 2025)
This study investigates the effects of calcination time, milling duration, and sintering temperature on the properties of Nickel oxide and Yttria-stabilized zirconia (NiO-YSZ) anode composite materials for solid oxide fuel cell (SOFC) applications. NiO nanoparticles were synthesized from nickel (II) sulfate (Ni(II)SO4), with X-ray diffraction (XRD) confirming a face-centered cubic (FCC) structure. The crystallite size (21 nm) was achieved after 8 hours of calcination, while prolonged durations caused particle agglomeration. Ball-milling for 12 hours produced comparatively fine particles with an average of 706 nm, though extended milling led to grain growth and aggregation. Scanning electron microscopy (SEM) revealed nano aggregation. Sintering at 1200 °C improved the densification of the NiO-YSZ layer while increasing its porosity, which enhanced the reduction of NiO to metallic nickel (Ni). Electrochemical Impedance Spectroscopy (EIS) demonstrated lower impedance and improved electrochemical performance for cells cold-sintered at 1200 °C. These findings show the importance of optimizing processing conditions to enhance the performance of NiO-YSZ anode for SOFCs, offering valuable insights for advanced energy conversion technologies.
Keywords: Cold-sintering; Mechano-chemical reaction; Nickel oxide; Solid oxide fuel cell; Yttria-stabilized zirconia